Influence and Screening of Potential Markers of Salmonella Pollution on Volatile Components of Pepper Chicken - Jie XU; Xiaoping FU; Yongsong ZHANG; Sujing LUO; BUHELIQI·Abudurexiti; Jiangchao WU; Siming ZHU (Shipin gongye ke-ji)
To explore the influence of Salmonella contamination on pepper chicken, electronic nose combined with headspace solid-phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS) technique was used to analyze volatile substances in pepper chicken contaminated with Salmonella at different concentration and culture time. The results showed that the electronic nose effectively differentiated volatile profiles across incubation periods. The contents of alcohols, ketones, alkanes and hydrides increased with the extension of culture time. Among them, W1W and W2S sensors were the indicator sensors of Salmonella contaminated pepper chicken in low concentration group, W6S and W1S sensors were the indicator sensors of Salmonella contaminated pepper chicken in high concentration group. Orthogonal partial least squares discriminant analysis (OPLS-DA) could better distinguish volatile substances in pepper chicken and classify the characteristic substances. HS-SPME-GC-MS identified 3-methyltetradecane (4 to 6 h after inoculation), chlorocetane (4 to 6 h after inoculation), 2-methyl-5-(1-methylvinyl)cyclohexanone and trans-4-(isopropyl)-1-methylcyclohexan-2-ene-1-ol (2 to 6 h after inoculation) could be used as a potential volatile marker of Salmonella contaminated pepper chicken. These results provide reference for the study of volatile markers of Salmonella contamination in pepper chicken.